IMPLEMENTASI SMART GOVERNMENT DI KANTOR LURAH GUNTUNG, KOTA BONTANG - Suci Azizah Febriyani; Dede Sri Kartini (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
This study analyzes how government support applications are in the context of smart government at the Guntung Lurah Office. The method used in this research is a qualitative research method with data collection techniques using observation, interviews and supporting documents the results of research on the implementation of smart government in Bontang City which was carried out at the Guntung Lurah Office was that there were 7 forms of smart government implemented. The implementation of smart government can be seen from the elements of successful e-government development, namely support, capacity to produce competent human resources, and value to produce benefits for society. The implementation of smart government has a positive impact on the community and employees, namely that the service process is not carried out manually, the community can access the information or documents needed, people who fall into the poor category can receive cash and non-cash assistance and the construction of facilities and infrastructure is carried out according to needs. However, the obstacles found in this research are the lack of outreach to the public and an internet network that does not support it, which has an impact on the use of applications and the service processes provided to the public. Key words: Smart government, e-government